Thermodynamic equilibrium analysis of combined carbon dioxide reforming with partial oxidation of methane to syngas - Saidina Amin, Nor Aishah (Pergamon-Elsevier Science Ltd, 2007)
The chemical equilibrium analysis on combined CH4-reforming with CO2 and O-2 (combined CORM-POM) has been conducted by total Gibbs energy minimization using Lagrange's undetermined multiplier method. The equilibrium compositions of the combined CORM-POM process were considerably influenced by CH4:CO2:O-2 feed ratios and operating temperatures. Methane oxidation reaction occurred predominantly at low temperatures, while the CO2 conversion was strongly influenced by the O-2/CH4 feed ratio. The addition of O-2 to the CORM process improved the CH4 conversion, H-2 and H2O yields and also the H-2/CO product ratio at the expense of CO2 conversion and CO yield. Accordingly, the optimal equilibrium conditions for the CH4:CO2:O-2 ratio were within the range of 1:0.8:0.2-1:1:0.2 and a minimum requirement temperature of 1000 K.